Orzeszkowej dialogi z tradycją: europejska literatura dawna = Orzeszkowa's dialogues with tradition: old European literature - Sikora, Ireneusz (1952-2016) (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The synthetic study brings effects of thorough analysis of Eliza Orzeszkowa's letters (gathered and published by Edward Jankowski in nine volumes) containing information on her reading experiences. As it appears, she read a lot and of course she was familiar with many outstanding literary or philosophical masterpieces.
Keywords: Orzeszkowa, Eliza (1841-1910); epistolografia - 19 w.; recepcja; dawna literatura europejska; epistolography; reception; old European literature